PENERAPAN MODEL TGT BERBANTUAN MEDIA KARTU PERTANYAAN UNTUK MENINGKATKAN HASIL BELAJAR IPAS KELAS IV DI SDN SUKORAME 2 - Cahyono, Arif Tri; Ilmawati Fahmi Imron; Nurul Mubarokah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve the learning outcomes of fourth-grade students at SDN Sukorame 2 Kota Kediri in the subject of Natural and Social Sciences (IPAS), specifically on the topic "Characteristics of Nature and Its Utilization," through the implementation of the Time Game Tournament model supported by question card media. The identified problem was the low level of student engagement in learning activities and suboptimal academic performance. This classroom action research was conducted in two cycles, each consisting of the stages of planning, implementation, observation, and reflection. Data were collected using student learning outcome tests. The results showed that in Cycle I, only 14 out of 28 students (50%) achieved the minimum mastery criteria, with an average score of 70.7. The learning process during this cycle was still teacher-centered and lacked active student participation. After improving the instructional strategy in Cycle II by applying the Time Game Tournament model and using question card media, student learning outcomes increased significantly. A total of 25 students (89.28%) achieved mastery, with the class average rising to 87, and only 3 students did not meet the criteria. This improvement indicates that the Time Game Tournament model, supported by question card media, effectively enhances active student participation, creates a more enjoyable learning environment, and has a positive impact on student achievement. Therefore, this model can serve as an effective alternative learning strategy to improve conceptual understanding among elementary school students.